2014
DOI: 10.1089/jmf.2013.3042
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Korean Traditional Diets in Hypertensive and Type 2 Diabetic Patients

Abstract: The prevalence of metabolic syndrome, hypertension, and diabetes has been increasing rapidly in Korea. The rate of increase has paralleled the replacement of Korean traditional diets (KTD), which emphasize vegetables and fermented foods, with western style dietary patterns that are rich in animal foods and saturated fat. We aimed to investigate the efficacy of the KTD in controlling fasting plasma glucose, blood pressure, and cardiovascular disease risk factors in hypertensive and type 2 diabetic (T2D) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 51 publications
1
46
0
1
Order By: Relevance
“…These findings are consistent with a controlled clinical trial that explored the effects of a traditional Korean diet compared with a control diet ("eat as usual") on cardiovascular risk factors in patients with diabetes and hypertension. In that study, adherence to a traditional Korean diet favorably influenced body composition (body weight, −2.3 kg; body mass index [BMI], −0.83 kg/m 2 ; body fat, −2.2%; p < 0.01), heart rate (−7.1 bpm; p = 0.002), and glycemic control (HbA1c, −0.72%; p = 0.003) [89].…”
Section: Traditional Asian Dietsmentioning
confidence: 96%
“…These findings are consistent with a controlled clinical trial that explored the effects of a traditional Korean diet compared with a control diet ("eat as usual") on cardiovascular risk factors in patients with diabetes and hypertension. In that study, adherence to a traditional Korean diet favorably influenced body composition (body weight, −2.3 kg; body mass index [BMI], −0.83 kg/m 2 ; body fat, −2.2%; p < 0.01), heart rate (−7.1 bpm; p = 0.002), and glycemic control (HbA1c, −0.72%; p = 0.003) [89].…”
Section: Traditional Asian Dietsmentioning
confidence: 96%
“…Lacti c acid from kimchi may prevent fat accumulation and obesityinduced heart diseases [Park et al, 2008]. Kimchi has been reported to have anti-obesity effects [Jung et al, 2014;Kim et al, 2011;Park et al, 2012]. Some studies have documented the protective effects of sauerkraut or sauerkraut juice against breast [Ju et al, 2000;Licznerska et al, 2013;Szaefer et al, 2015] and colon [Kusznierewicz et al, 2010] cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Song and Joung [ 5 ] further showed that the Korean traditional dietary patterns have been associated with a decreased incidence of metabolic abnormalities, such as high blood pressure and dyslipidemia. Favorable changes in cardiovascular risk factors have been reported by regular consumption of a Korean traditional diet for 12 wk in hypertensive and diabetic patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%